Behavioral and Socio-Economic Determinants of Antimicrobial Resistance in Sub-Saharan Africa: A Systematic Review - Kapatsa T; Lubanga AF; Bwanali AN; Harawa G; Mudenda S; Chipewa PC; Kamayani M; Makole TJ; Ali AY; Mohamed AA; Tae Youn K; Kim L; et al. (Infection and Drug Resistance, 2025)
Thandizo Kapatsa,1,2 Adriano Focus Lubanga,1,3 Akim N Bwanali,1,4 Gracian Harawa,5,6 Steward Mudenda,7 Pascal C Chipewa,8 Mapeesho Kamayani,9 Tumaini John Makole,10 Abdisalam Yusuf Ali,11 Abdullahi Abdirasak Mohamed,12,13 Kim Tae Youn,14 Lorie Kim,14 Won D Daniel,14 Matthew Kim,14 Tarek Emir Chehab,15 Thomas Nyirenda16,17 1Education and Research, Clinical Research Education and Management Services (CREAMS), Lilongwe, Malawi; 2Department of Laboratory Science, Dedza District Hospital, Ministry of Health, Dedza, Malawi; 3Department of Clinical Services, Kamuzu Central Hospital, Lilongwe, Malawi; 4Department of Clinical Services, Queen Elizabeth Central Hospital, Blantyre, Malawi; 5National Antimicrobial Resistance Coordinating Center, Public Health Institute of Malawi, Lilongwe, Malawi; 6Society of Medical Doctors (SMD), Lilongwe, Malawi; 7Department of Pharmacy, School of Health Sciences, University of Zambia, Lusaka, Zambia; 8Malaria Alert Centre, Kamuzu University of Health Sciences, Blantyre, Malawi; 9Churches Health Association of Zambia, Lusaka, Zambia; 10Pharmacy Council of Tanzania, Dar Es Salaam, Tanzania; 11School of Public Health, Mount Kenya University, Nairobi, Kenya; 12School of Postgraduate Studies, Benazir University, Mogadishu, Somalia; 13Department of Global Health and Development, London School of Hygiene and Tropical Medicine, London, UK; 14Youth With Talents, Fairfax, VA, USA; 15Koc University School of Medicine, Instanbul, Turkey; 16European and Developing Countries Clinical Trials Partnership (EDCTP), Strategic Partnerships and Capacity Development, Cape Town, South Africa; 17Department of Global Health, Stellenbosch University, Cape Town, South AfricaCorrespondence: Thandizo Kapatsa, Department of Laboratory Sciences, Dedza District Hospital, Post Office Box 136, Dedza, Malawi, Email thandizokapatsa@gmail.comIntroduction: Antimicrobial resistance (AMR) is currently one of the twenty-first century’s biggest threats to public health. Addressing AMR is often operationalized as requiring ‘behavior change’ of clinicians and patients and improving the drug development pipeline. Few studies and interventions have approached AMR as a challenge fundamentally embedded within the cultural fabric of modern societies and their varied economic, social and political organizations. This systematic review aimed to gather and review the available data on the behavioral and socio-economic determinants of AMR in sub-Saharan Africa (SSA).Methods: Articles were sourced from PubMed using search terms across five domains: “Antimicrobial resistance”, “Sub-Saharan Africa”, “Behavioral”, “Socio-economic”, and specific SSA country names. References were also reviewed for relevant data. This systematic review included original studies published in English between 2015 and 2023, focusing on behavioral and socio-economic factors influencing AMR in human populations in SSA, with AMR as a key outcome.Results: This systematic review identified 30 studies, with 83% (n=25) focusing on self-medication and antibiotic use practices, 67% (n=20) on healthcare providers’ practices and knowledge, and 60% (n=18) on community knowledge and perceptions of AMR while 50% (n=15) of studies explored various socio-economic factors. The common themes that emerged from these studies included inadequate evidence-based prescription practices (63%, n=19), financial barriers to accessing antibiotics (50%, n=15), poor community awareness of AMR (53%, n=16), regulatory challenges in antibiotic sales and distribution (47%, n=14), and healthcare infrastructure limitations, including deficient diagnostic capabilities and antimicrobial stewardship programs (40%, n=12).Conclusion: This review’s findings provide crucial insights into the behavioral and socioeconomic patterns influencing AMR in sub-Saharan African populations. For AMR interventions to be effective, there is a need for a thorough understanding of people’s behaviors and practices about AMR knowledge and antimicrobial use which will help in developing more targeted interventions and policies to address inappropriate antimicrobial use and the spread of AMR.Keywords: antimicrobial resistance, behavioral determinants, socio-economic determinants, sub-Saharan Africa